Increased clonal growth in heavily harvested ecosystems failed to rescue ayahuasca lianas from decline in the Peruvian Amazon rainforest - Coe, Michael A.; Gaoue, Orou G. (The Journal of applied ecology, 2023)
Increasing harvest and overexploitation of wild plants for non‐timber forest products can significantly affect population dynamics of harvested populations. While the most common approach to assess the effect of harvest and perturbation of vital rates is focused on the long‐term population growth rate, most management strategies are planned and implemented over the short‐term. We developed an integral projection model to investigate the effects of harvest on the demography and the short‐ and long‐term population dynamics of Banisteriopsis caapi in the Peruvian Amazon rainforest. Harvest had no significant effect on the size‐dependent growth of lianas, but survival rates increased with size. Harvest had a significant negative effect on size‐dependent survival where larger lianas experienced greater mortality rates under high harvest pressure than smaller lianas. In the populations under high harvest pressure, survival of smaller lianas was greater than that of populations with low harvest pressure. Harvest had no significant effect on clonal or sexual reproduction, but fertility was size‐dependent. The long‐term population growth rates of B. caapi populations under high harvest pressure were projected to decline at a rate of 1.3% whereas populations with low harvest pressure are expected to increase at 3.2%. However, before reaching equilibrium, over the short‐term, all B. caapi populations were in decline by 26% (high harvested population) and (low harvested population) 20.4% per year. Elasticity patterns were dominated by survival of larger lianas irrespective of harvest treatments. Life table response experiment analyses indicated that high harvest caused the 6% reduction in population growth rates by significantly reducing the survival of large lianas and increasing the survival‐growth of smaller lianas including vegetative reproductive individuals. Synthesis and applications . This study emphasizes how important it is for management strategies for B. caapi lianas experiencing anthropogenic harvest to prioritize the survival of larger size lianas and vegetative reproducing individuals, particularly in increased harvested systems often prone to multiple stressors. From an applied conservation perspective, our findings illustrate the importance of both prospective and retrospective perturbation analyses in population growth rates in understanding the population dynamics of lianas in general in response to human‐induced disturbance. El aumento de la recolección y la sobreexplotación de plantas silvestres para la obtención de productos forestales no madereros pueden afectar significativamente a la dinámica poblacional de las poblaciones recolectadas. Aunque el enfoque más común para evaluar el efecto de la recolección y la perturbación de las tasas vitales se centra en la tasa de crecimiento de la población a largo plazo, la mayoría de las estrategias de gestión se planifican y aplican a corto plazo. Desarrollamos un modelo de proyección integral para investigar los efectos de la cosecha sobre la demografía y la dinámica poblacional a corto y largo plazo de Banisteriopsis caapi en la selva amazónica peruana. La cosecha no tuvo un efecto significativo en el crecimiento de las lianas en función del tamaño, pero las tasas de supervivencia aumentaron con el tamaño. La cosecha tuvo un efecto negativo significativo en la supervivencia dependiente del tamaño, donde las lianas más grandes experimentaron mayores tasas de mortalidad bajo alta presión de cosecha que las lianas más pequeñas. En las poblaciones sometidas a alta presión de recolección, la supervivencia de las lianas más pequeñas fue mayor que la de las poblaciones con baja presión de recolección. La cosecha no tuvo un efecto significativo sobre la reproducción clonal o sexual, pero la fertilidad fue dependiente del tamaño. Se prevé que las tasas de crecimiento a largo plazo de las poblaciones de B. caapi sometidas a una alta presión de recolección disminuyan a un ritmo del 1,3%, mientras que se espera que las poblaciones sometidas a una baja presión de recolección aumenten a un ritmo del 3,2%. Sin embargo, antes de alcanzar el equilibrio, a corto plazo, todas las poblaciones de B. caapi disminuyeron un 26% (población sometida a alta recolección) y (población sometida a baja recolección) un 20,4% al año. Los patrones de elasticidad estuvieron dominados por la supervivencia de las lianas más grandes, independientemente de los tratamientos de recolección. Los análisis del experimento de respuesta de la tabla de vida indicaron que la cosecha alta causó la reducción del 6% en las tasas de crecimiento de la población al reducir significativamente la supervivencia de las lianas grandes y aumentar la supervivencia‐crecimiento de las lianas más pequeñas, incluidos los individuos reproductivos vegetativos. Síntesis y aplicaciones. Este estudio subraya la importancia de que las estrategias de gestión de las lianas B. caapi sometidas a recolección antropogénica den prioridad a la supervivencia de las lianas de mayor tamaño y de los individuos reproductores vegetativos, particularmente en sistemas de recolección creciente a menudo propensos a múltiples factores de estrés. Desde una perspectiva de conservación aplicada, nuestros resultados ilustran la importancia de los análisis prospectivos y retrospectivos de las perturbaciones en las tasas de crecimiento de la población para comprender la dinámica de la población de lianas en general en respuesta a las perturbaciones inducidas por el hombre.